Wybrane modele ekonometryczne w badaniach dochodowej elastyczności popytu konsumpcyjnego - Kurzawa, Izabela; Wysocki, Feliks (Selected Econometric Models Used in the Examination of Income Demand Elasticity, 2009)
This research presents the usefulness of chosen econometric models (demand functions) to investigate income demand elasticity of food-stuffs. Elasticity was calculated on the basis of estimated demand functions: linear, double logarithmic, logarithmic, Working, Working-Leser and Törnquist. This research project is based on micro-economic data concerning budgets of individual Polish households which were gathered by Central Statistical Office of Poland in 2003. The analyzed annual sample contains 32452 households. It was noticed that the choice of relevant demand function does not only relay on statistical fitting of model. It should also depend on reasonable content-related elasticity of the model used (compliance with consumer's theory) and the character of product (basic, higher or luxurious goods). Demand functions such as Working, Törnquist (I) or Törnquist (II) are preferred to research Engel's dependence for food-stuffs. The logarithmic function is used exceptionally. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 70-78